Real-time deformability cytometry as a label-free indicator of cell function - Otto, O.; Rosendahl, P.; Golfier, S.; Mietke, A.; Herbig, M.; Jacobi, A.; Topfner, N.; Herold, C.; Klaue, D.; Girardo, S.; Winzi, M.; Fischer-Friedrich, E.; et al. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2015)
The mechanical properties of cells are known to be a label-free, inherent marker of biological function in health and disease. Wide-spread utilization has so far been impeded by the lack of a convenient measurement technique with sufficient throughput. To address this unmet need, we have recently introduced real-time deformability cytometry (RT-DC) for continuous mechanical single-cell classification of heterogeneous cell populations at rates of several hundred cells per second. Cells are driven through the constriction zone of a microfluidic chip leading to cell deformations due to hydrodynamic stresses only. Our custom-built image processing software performs image acquisition, image analysis and data storage on the fly. The ensuing deformations can be quantified and an analytical model enables the derivation of cell material properties. Performing RT-DC we highlight its potential to identify rare objects in heterogeneous suspensions and to track drug-induced changes in cells. In summary, RT-DC enables marker-free, quantitative phenotyping of heterogeneous cell populations with a throughput comparable to standard flow cytometry.
CRIS-Team Scopus Importer:2022-08-05